Analytical determination of speed-torque and speed-current curves of single-cage induction motor under supply voltage and frequency variations. Issue 6 (18th September 2018) - Aree, Pichai
Abstract : Purpose: An important characteristic of most induction motors is speed- or slip-torque curve. A simplified Kloss formula is widely used for describing speed-torque characteristic because it is fairly simple. Only two parameters related to break-down torque and break-down slip are regarded as input parameters. Because this simplified formula ignores an unknown parameter that is a ratio between Thevenin's and rotor resistances, an accurate torque curve characteristic may not be fully obtained over an entire speed range. Moreover, the conventional Kloss formula does not offer a speed-torque curve calculation when motor's supply voltages and frequencies are deviated from rated values. Hence, the purpose of this paper is to present an extension of Kloss formula, which allows a more precise estimation of speed-torque and speed-current curves of single-cage three-phase induction motors over a wide range of speeds at different motor's operating voltages, frequencies and rotor-circuit resistances. Design/methodology/approach: The analytical approach is mainly used for determining all key parameters in the Kloss formula using a known set of data such as rated torque, starting torque, break-down torque and rated speed, in which they can be obtained from motor's manufacturer. Findings: The speed-torque and speed-current curves taken from laboratory measurements are compared with those from the calculations. Good agreements between them are fully observed. Originality/value: This analytical approach is useful in providing an accurate speed-torque and speed-current curves required for most steady-state analysis.